A 3‐Decade, Single‐Center Experience of Liver Transplantation for Cholangiocarcinoma: Impact of Era, Tumor Size, Location, and Neoadjuvant Therapy. Issue 3 (21st October 2021) - Ito, Takahiro; Butler, James R.; Noguchi, Daisuke; Ha, Minah; Aziz, Antony; Agopian, Vatche G.; DiNorcia, Joseph; Yersiz, Hasan; Farmer, Douglas G.; Busuttil, Ronald W.; Hong, Johnny C.; Kaldas, Fady M.
Abstract : Liver transplantation (LT) for cholangiocarcinoma (CCA) remains limited to a small number of centers. Although the role of neoadjuvant therapy (NAT) has been explored over time, an in‐depth analysis of NAT strategies remains limited. Furthermore, controversy exists regarding acceptable tumor size during patient selection for LT. This study explores the impact of era, tumor size, and NAT strategy on LT outcomes for CCA. We conducted a retrospective review of 53 patients with CCA treated with LT from 1985 to 2019; 19 hilar CCA (hCCA) and 30 intrahepatic CCA (iCCA) were included. The relative contributions of varying NAT (neoadjuvant chemotherapy [NAC], neoadjuvant local therapy [NALT], and combined NAC and NALT [NACLT]) as well as the implication of tumor size and era were analyzed. The primary endpoint was overall survival (OS). Compared with the old era (1985‐2007), 5‐year OS in patients who underwent LT in the recent era (2008‐2019) showed a superior trend. The 5‐year OS from initial treatment in patients receiving NACLT for hCCA and iCCA were 88% and 100% versus 9% and 41% in patients without it, respectively ( P = 0.01 for hCCA; P = 0.02 for iCCA), whereas NAC or NALT alone did not show significant differences in OS versus no NAT ( P > 0.05). Although 33 patients had large‐size tumors (hCCA ≥ 30 mm, n = 12, or iCCA ≥ 50 mm, n = 21), tumor size had no impact on survival outcomes. Outcomes of LT for CCA seem to have improved over time. Multimodal NAT is associated with improved survival in LT for both iCCA and hCCA regardless of tumor size.